HUBUNGAN REGULASI DIRI DENGAN FEAR OF MISSING OUT PADA MAHASISWA BARU PENGGUNA APLIKASI TIKTOK - Handayani, Anifa; Aviani, Yolivia Irna (CAUSALITA : Journal of Psychology, 2023)
In today's modern era, social media is not just a medium for finding information, but also provides an opportunity for everyone to be able to see and find out what activities are carried out by other people on social media and find out valuable activities carried out by other people and compare with the experience of the individual. With this, there will be anxiety and fear of not being connected to each other with activities carried out by other people on social media, which is better known as Fear Of Missing Out (FoMo). At this time, first-year students need a good pattern of self-regulation, or better known as self-regulation. With good self-regulation, efforts are made to provide good learning patterns and interaction patterns while sitting on the lecture bench. The purpose of this study is to find out whether there is a relationship between self-regulation and fear of missing out (FoMo) in new students who use the Tiktok application. The population is 46,456 students, and as many as 348 students become the research sample, using purposive sampling technique. This study uses two scales, namely the self-regulation scale (9 items) and the Fear Of Missing Out (FoMo) scale (10 items). Correlation analysis shows a negative relationship between Self-Regulation and FoMo (rxy = -119 with a value of p = 0.026 (p <0.05), this means that the higher the FoMo, the lower the Self-Regulation, vice versa the lower the FoMo, the higher Self Regulation for new students using the Tiktok application. Keywords: Self-Regulation, Fear of Missing Out (FoMo), New Students